The irreducibility of the human person: a Catholic synthesis - Spencer, Mark K. (The Catholic University of America Press, 2022)
"This book presents a philosophical portrait of human persons that depicts each way in which we are irreducible, with the goal of guiding the reader to perceive, wonder at, and love all the unique features of human persons. It builds this portrait by showing how claims from many strands of the Catholic tradition can be synthesized. These strands include Thomism, Scotism, phenomenology, personalism, nouvelle théologie, analytic philosophy, and Greek and Russian thought. The book focuses on how these traditions' claims are grounded in experience and on how they help us to perceive irreducible features of persons. This book also explores irreducible features of our subjectivity, senses, intellect, freedom, and affections, and of our souls, bodies, and activities"--